1989
DOI: 10.5271/sjweh.1836
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sciatic pain among concrete reinforcement workers and house painters--a five-year follow-up.

Abstract: RIIHIMAKI H, WICKSTROM G, HANNINEN K, LUOPAJARVI T . Predictors of sciatic pain among concrete reinforcement workers and house painter s -a five-year follow-up. Scand J Work En viron Health 1989;15:415-423. In a study of the assoc iation of occupation and several other determinants with the occurrence of sciatic pain, 167 concrete reinforcement workers and 161 house painters were follow ed for five years. Base-line data were obtained with a questionnaire, an interview on back symptoms, a clinical exam ination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…A similar result has been reported concerning neck pain (26) and sciatica (27). This information may be of importance for an occupational health physician when making clinical decisions.…”
Section: Discussionsupporting
confidence: 70%
“…A similar result has been reported concerning neck pain (26) and sciatica (27). This information may be of importance for an occupational health physician when making clinical decisions.…”
Section: Discussionsupporting
confidence: 70%
“…One recent study of construction workers reported that progressive degenerative spinal changes were associated with an increased risk of sciatic pain (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been found in many studies to be related to the occurrence of back disorders (38, 69, 79, 89,91 , 122, 126, 137, 138), but there are also studies which have failed to show such a relationship (115). There is experimental evidence that smoking impairs the nutrition of the intervertebral discs however (139).…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…In some studies (69,97,115,124) taller people have been found to be at greater risk for low-back pain, but not in others (38,73,84,125). Likewise, a positive relation between excess body weight and risk for low-back disorders was shown in some studies (97,122,124,126) but not in others (38,69,125,127).…”
Section: Individual Characteristicsmentioning
confidence: 99%